The Epiphanies of life: The works of Patrizia Cavalli and Lisetta Carmi (Balthazar, 2022)
This paper aims to define the impact of the early works of Patrizia Cavalli and Lisetta Carmi on the generations born between the 1960s and the 1980s, who lived their youth in Italian provincial cities.
Keywords: Patrizia Cavalli; Lisetta Carmi; poetry; art; photography; society